Cognitive academic language learning approach calla and its influence on the academic proficiency of a world history class in 8th to 10th grades at unidad educativa Steiner internacional - Delgado Vera, Sara Azalia (2016)
The lack of learning strategies in teachers’ instruction causes students from 8to 10 grades level A a lower academic performance in the World History Class at Unidad Educativa Steiner Internacional. As a result of this lack of strategy instructions, students are not able to effectively improve their academic proficiency throughout the school year…..